2016
DOI: 10.1093/nop/npw013
|View full text |Cite
|
Sign up to set email alerts
|

Core deficits and quality of survival after childhood medulloblastoma: a review

Abstract: Background. Medulloblastoma is the most common malignant central nervous system tumor in children. Treatment most often includes surgical resection, craniospinal irradiation, and adjuvant chemotherapy. Although survival has improved dramatically, the tumor and its treatments have devastating long-term side effects that negatively impact quality of survival (QoS). The objective was to review the literature on QoS following childhood medulloblastoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 151 publications
4
66
0
4
Order By: Relevance
“…Roughly 20-40% of children experiencing TBI between 5-15 years of age show significant executive dysfunction within the first year of injury (Sesma, Slomine, Ding, & McCarthy, 2008). In studies of EFs following childhood ABI, impairments have been found across the entire range of executive constructs (Beauchamp et al, 2011;Chevignard et al, 2016;Chevignard et al, 2017;Greenham et al, 2017;Krasny-Pacini et al, 2016). Specifically, EFs consisting of self-generative behavior, flexibility, set shifting, mental control, attention, and selfmonitoring are commonly impaired in pediatric populations following TBI (Baron, 2004;Chevignard et al, 2017;Gioia, Isquith, & Guy, 2001;Krasny-Pacini et al, 2016;Shultz et al, 2016) with persistent difficulties documented up to 10 years post-injury (Beauchamp et al, 2011).…”
Section: Abi During Childhood Can Be Associated With Enduring Difficumentioning
confidence: 99%
See 2 more Smart Citations
“…Roughly 20-40% of children experiencing TBI between 5-15 years of age show significant executive dysfunction within the first year of injury (Sesma, Slomine, Ding, & McCarthy, 2008). In studies of EFs following childhood ABI, impairments have been found across the entire range of executive constructs (Beauchamp et al, 2011;Chevignard et al, 2016;Chevignard et al, 2017;Greenham et al, 2017;Krasny-Pacini et al, 2016). Specifically, EFs consisting of self-generative behavior, flexibility, set shifting, mental control, attention, and selfmonitoring are commonly impaired in pediatric populations following TBI (Baron, 2004;Chevignard et al, 2017;Gioia, Isquith, & Guy, 2001;Krasny-Pacini et al, 2016;Shultz et al, 2016) with persistent difficulties documented up to 10 years post-injury (Beauchamp et al, 2011).…”
Section: Abi During Childhood Can Be Associated With Enduring Difficumentioning
confidence: 99%
“…Children who sustain ABI are likely to exhibit physical, neurological, cognitive, emotional, psychosocial and behavioral impairments (Greenham, Anderson, & Mackay, 2017), such as epilepsy, impaired cognition (Chevignard, Câmara-Costa, Doz, & Dellatolas, 2016) or communication (Doser, Poulsen, & Norup, 2015), post-traumatic stress disorder (PTSD) (Von Steinbuechel et al, 2016), or depression (Letkiewicz et al, 2014). They are also likely to be bullied, to bully others, and to display violent as well as non-violent conduct behaviors (Ilie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…post-operative cerebellar mutism, ataxia) and treatment-related factors (e.g. radiation dose and volumes) 30 . Thus, the influence of these factors should be considered when examining QoS.…”
Section: Nop-d-16-00037r2mentioning
confidence: 99%
“…Similarly, in the present study, the association of these complications was moderate with IQ measures, whereas it was non-significant with the questionnaire-based measures. However, a negative influence of post-operative complications on QoS assessed through questionnaires has been reported, although their influence on psychosocial domains seems to be less pronounced and has been less frequently studied 30 .…”
Section: Nop-d-16-00037r2 Questionnaire-based Qos and Cognitive Perfomentioning
confidence: 99%